Improvement of Sporobolomyces ruberrimus carotenoids production by the use of raw glycerol. (January 2016) - Cardoso, L.A.C.; Jäckel, S.; Karp, S.G.; Framboisier, X.; Chevalot, I.; Marc, I.
Highlights: Sporobolomyces ruberrimus H110 produced carotenoids from glycerol with high yield. Carotenoids were identified as torularhodin, torulene, β-carotene and γ-carotene. Raw glycerol presented higher yield and productivity when compared to pure glycerol. Addition of fatty acids to pure glycerol was beneficial for yield and productivity. The presence of some fatty acids improved the proportion of torularhodin. Abstract: The red yeast Sporobolomyces ruberrimus H110 was able to use glycerol as a carbon source. The highest concentration (0.51 g L −1 ) and productivity (0.0064 g L −1 h −1 ) of carotenoids were achieved when raw glycerol from biodiesel production, containing around 1 g L −1 of fatty acids, was used as the carbon source, which represented increases of 27% and 1.5×, respectively, in relation to pure glycerol. Mass spectrometry analysis led to the identification of four carotenoids in the fermented samples, torularhodin, torulene, β-carotene and γ-carotene. The use of raw glycerol also enhanced the proportion of torularhodin (69% against 59% in pure glycerol). The addition of individual fatty acids (palmitic, stearic, oleic and linoleic acids) to pure glycerol resulted in increases between 15% and 25% in maximum concentration and between 1.6 × and 2.0× in productivity of carotenoids. The presence of palmitic and oleic acids increased the torularhodin proportion to 66%.